1979
DOI: 10.3109/00498257909038714
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [14C]phenol by sheep, pig and rat

Abstract: 1. Following an oral dose of [14C]phenol (12.5 or 25 mg/kg) to sheep, pig and rat, urinary elimination of radioactivity was rapid, 80-90% dose being excreted in the first 8 h. 2. In anaesthetized, ureter-cannulated rats, 70-80% of an intraduodenal dose was eliminated in 2 h; 2% dose was excreted as phenol conjugates in the urine within 10 min. 3. The major urinary metabolites from phenol (25 mg/kg) were phenylglucuronide and phenylsulphate. In the sheep, pig and rat, the glucuronide accounted for 49%, 83% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…Kao et al (1979) reported that phenyl glucuronide and phenyl sulfate were the major metabolites for the rat and sheep, with sulfate and glucuronide conjugates of quinol as the minor constituents. Unlike rodents, sheep were found to excrete phenyl and quinol phosphates.…”
Section: Health Effectsmentioning
confidence: 99%
“…Kao et al (1979) reported that phenyl glucuronide and phenyl sulfate were the major metabolites for the rat and sheep, with sulfate and glucuronide conjugates of quinol as the minor constituents. Unlike rodents, sheep were found to excrete phenyl and quinol phosphates.…”
Section: Health Effectsmentioning
confidence: 99%
“…Enzymic cleavage of sulphate and glucuronic acid conjugates was carried out according to Kao et al (1979). Acid hydrolysis was carried out following the method of Carton et al (1949).…”
Section: Identification Of Metabolitesmentioning
confidence: 99%
“…Sulfation is one of the primary routes for conjugation of phenolic compounds in ruminants (Grant, 1948;Kao, Bridges, & Faulkner, 1979;Brewington, Parks, & Schwartz, 1973, 1974. Recent studies in this laboratory indicated that species-related alkylphenols, including p-and m-cresols and 3-and 4-ethylphenols in ruminant milks, were present predominantly as sulphate esters (Lopez & Lindsay, 1993;Kilic & Lindsay, 2005).…”
Section: Introductionmentioning
confidence: 97%